Use of deeper plantar flexor muscles in low torque isometric and concentric plantar flexion tasks - Oksanen, Hermanni (2016)
Coordination of a task such as plantar flexion might seem simple, but is in reality achieved through the activation of several muscles—muscles that play an important role in locomotion and posture control. These can be divided in to two groups, superficial and deep plantar flexors. It has been shown that although people usually produce certain well learned movements very similarly, some variability in the coordination might occur. This is also the case with the ankle plantar flexors as shown by Finni et al. (2006) and Masood et al (2014). Purpose of the study was to examine whether some individuals use their deeper plantar flexors to a greater extent than others and to see whether the relative contribution of the deeper muscles is affected by the type of movement or torque level. The two methods of measuring muscle activity, EMG and VE-PC MRI, were also compared. Fifteen subjects took part in two measurement sessions where the activity of the plantar flexor muscles was measured. The first session took place in a biomechanics laboratory where EMG data from gastrocnemius medialis, soleus and flexor hallucis longus was recorded. The other session was done in the MRI scanner and produced muscle tissue velocity data for the same three muscles. Subjects did both isometric and concentric plantar flexion tasks at torque levels of 10% MVC and 30% MVC. The relative contribution of the deeper muscles was assessed by calculating velocity ratios between GM and FHL as well as Sol and FHL. Clear differences were found between individuals. The lowest ratios, indicating greater activity of deep muscles were 1.02 for GM/FHL and 1.09 for Sol/FHL, whereas, the highest ratios were 2.08 and 2.44 respectively. At 10% torque level the two different movement types differed slightly. For GM/FHL velocity ratio was 0.41 (p<0.05), and for Sol/FHL 0.38 (p=0.68) smaller in isometric task compared to concentric. Torque level had no effect on the relative contribution of the deeper muscles. For GM (r=0.52, p<0.001) and FHL (r=0.59, p<0.001) there was a correlation between the EMG and peak mean negative velocity. The correlation between peak mean negative velocity and torque, and EMG and torque were also similar to each other. Differences in velocity ratios show that individuals use their deeper plantar flexors to different extent. Some of the subjects showed little to no movement in the deeper muscles whereas others had equal peak mean velocities in the deeper muscles. With the conflicting results no clear conclusion can be drawn on whether torque or type of movement affect the relative contribution of the deeper muscles. The two measurement methods yielded similar results and there was also a correlation between peak mean velocity and EMG for GM and FHL.